PENGARUH PERBANDINGAN TEMPURUNG KELAPA DAN ECENG GONDOK SERTA VARIASI UKURAN PARTIKEL TERHADAP KARAKTERISTIK BRIKET - Iriany, Firman Abednego Sarwedi Sibarani, Meliza (Jurnal Teknik Kimia USU, 2016)
This research used raw material water hyacinth and coconut shell. The purpose of this research is to get briquettes with high heating value and to obtain briquettes with good quality. Comparison of the base material mixed water  hyacinth and coconut shell in this research is 1:1, 1:2, 1:3, 1:4 with variations in particle size of 10 mesh, 42 mesh and 60 mesh, and using an adhesive tapioca 10% from the weight of raw material. The results of measurement in this research was compared to the quality parameters  such as SNI, Japan standard, British, and America. The survey results revealed that the ideal composition made from a mixture of water hyacinth and coconut shell is briquette in comparison 1:4 with particle size 60 mesh and have the highest of heating value is 6.851,3311 cal/g, the lowest ash content is 8,1918%, the lowest of moisture content is 1,0140%,  levels of substance evaporates is 13,7890%, the value of density is 0.9836 g/cm3, the firing rate is 2,9x10 -3 g/sec and the compressive strength is 11,3234 kg/cm2. The results are in accordance to SNI, Japan standard, British, and America, while the compression pressure of briquette only accordance to British standard.